Impact of the response to platinum-based chemotherapy on the second-line immune checkpoint inhibitor monotherapy in non-small cell lung cancer with PD-L1 expression ≤49%: a multicenter retrospective study - Yoshimura, Akihiro; Takeda, Takayuki; Kataoka, Nobutaka; Tanimura, Keiko; Fukui, Mototaka; Chihara, Yusuke; Takei, Shota; Kawachi, Hayato; Nakanishi, Kentaro; Yamanaka, Yuta; Tamiya, Nobuyo; Honda, Ryoichi; et al. (Frontiers in Oncology, 2024)
The efficacy of second-line immune checkpoint inhibitor (ICI) therapy is limited in non-small cell lung cancer (NSCLC) patients with ≤ 49% PD-L1 expression.Although chemoimmunotherapy is a promising strategy, platinum-based chemotherapy followed by ICI monotherapy is often used to avoid synergistic adverse events. However, predictors of the efficacy of ICI monotherapy after platinum-based chemotherapy in NSCLC with ≤ 49% PD-L1 expression remain scarce.Methods: This multicenter retrospective study evaluated 54 advanced or recurrent NSCLC patients with ≤ 49% PD-L1 expression who were treated with second-line ICI monotherapy following disease progression on first-line platinum-based chemotherapy at nine hospitals in Japan. The impact of response to platinum-based chemotherapy on the efficacy of subsequent ICI monotherapy was investigated.The response to first-line platinum-based chemotherapy was divided into two groups: the non-progressive disease (PD) group, which included patients who did not experience disease progression after four cycles of chemotherapy, and the PD group, which included patients who showed initial PD or could not maintain disease control during the four cycles of chemotherapy and switched to second-line ICI monotherapy.Among the 54 patients, 32 and 22 were classified into the non-PD and PD groups, respectively. The non-PD group showed better response rates (p = 0.038) and longer overall survival (OS) with ICI monotherapy (p = 0.023) than the PD group. Multivariate analysis identified that maintaining a non-PD status after four cycles of chemotherapy was an independent prognostic factor for ICI monotherapy (p = 0.046). Moreover, patients with a modified Glasgow Prognostic Score (mGPS) of 0 showed a tendency for longer OS with ICI monotherapy (p = 0.079), and there was a significant correlation between maintaining non-PD after four cycles of chemotherapy and an mGPS of 0 (p = 0.045).Conclusions: Maintaining a non-PD status after four cycles of platinum-based chemotherapy was a predictor of OS after second-line ICI monotherapy. These findings will help physicians select the most suitable treatment option for NSCLC patients who were treated with platinum-based chemotherapy and switched to second-line treatment.Those who experienced early PD during platinum-based chemotherapy should not be treated with ICI monotherapy in the second-line setting.